The Teacher’s Paradigm to Learning in The Independent Curriculum at Elementary School: A Study in Jayapura City - Efendi, Didik (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The independent curriculum provides teachers with the opportunity to innovate in the learning process. As a replacement for the 2023 curriculum, the independent curriculum has a different paradigm from the previous curriculum, namely emphasizing teacher independence to manage learning with a focus on student achievement. This research uses a qualitative approach and descriptive research type to describe the SD/MI teacher paradigm regarding Independent Curriculum learning in Jayapura City. This research was conducted at MIN Jayapura City. Techniques for collecting research procedures through observation, in-depth interviews and documentation. Meanwhile, the analysis method uses the Creswel model analysis technique. The research results show that the SD/MI teachers' paradigm regarding learning in the independent curriculum is as follows: (1) Independent curriculum-based learning emphasizes the achievement of learning outcomes (CP) at each phase rather than at each grade level; (2) Teachers have more freedom in managing learning; (3) Learning must be relevant to the needs and characteristics of students; (4) Technology-based learning; (5) An independent curriculum requires teacher collaboration; (6) Learning oriented towards developing the Pancasila Student Profile and Rahmatan Lil Alamin Student Profile (P5 PPRA); (7) The independent curriculum emphasizes differentiated learning.